In situ amplification of visna virus DNA in tissue sections reveals a reservoir of latently infected cells - Staskus, Katherine A.; Couch, Leslie; Bitterman, Peter; Retzel, Ernest F.; Zupancic, Mary; List, James; Haase, Ashley T. (Microbial pathogenesis, 1991)
Maedi and visna are, respectively, the pulmonary and neurological manifestations of slowly progressive infections of sheep caused by retroviruses of the lentivirus subfamily. Lentivirus infections are also persistent infections in which host defenses are generally not successful in eliminating the infectious agent because of restricted viral gene expression in many infected cells. In this report, we describe a method for amplifying and detecting viral DNA in tissue sections which has made it possible to verify experimentally the postulated existence of this reservoir of latently infected cells, as well as to estimate the actual number of cells which harbor viral genomes in infected tissues. In the discussion, we present a simple mathematical model that relates this number to the rate at which inflammatory lesions develop. This model can account for both the slow progression of natural infections and for the rapid accumulation of inflammatory foci in the high dosage experimental system analysed in our studies.